Analysis of Student Errors in Solving HOTS-Type Sequence and Series Problems Based on Newman Error Analysis - Risky Illaina Septia Putri; Ratri Candra Hastari (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
This study aims to analyze student errors in solving HOTS-type math problems using Newman's stages on sequence and series material. This research is qualitative. The subject of this research is class X DPIB 1 SMK